Sarah Schenirer and the Bais Yaakov movement : a revolution in the name of tradition - Seidman, Naomi (Littman library of Jewish civilization (Series), 2019)
"National Jewish Book Awards 2019 Winner of the Barbara Dobkin Award for Women's Studies and Finalist for Education and Jewish Identity. Sarah Schenirer is one of the unsung heroes of twentieth-century Orthodox Judaism. The Bais Yaakov schools she founded in interwar Poland had an unparalleled impact on a traditional Jewish society threatened by assimilation and modernity, educating a generation of girls to take an active part in their community. The movement grew at an astonishing pace, expanding to include high schools, teacher seminaries, summer programmes, vocational schools, and youth movements, in Poland and beyond; it continues to flourish throughout the Jewish diaspora. Naomi Seidman explores the movement through the tensions that characterized it, capturing its complexity as a revolution in the name of tradition. She presents the context which led to its founding, examining the impact of socialism, feminism, Zionism, and Polish electoral politics on the process, and recounts its history, from its foundation in interwar Kraków to its near-destruction in the Holocaust, and its role in the reconstruction of Orthodoxy in subsequent decades. A vivid portrait of Schenirer shines through. The book includes selections from her writings published in English for the first time. Her pioneering, determined character remains the subject of debate in a culture that still regards innovation, female initiative, and women's Torah study with suspicion."--ProQuest website.